If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -10 = 7a Reorder the terms: -10 + 5a = 7a Solving -10 + 5a = 7a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7a' to each side of the equation. -10 + 5a + -7a = 7a + -7a Combine like terms: 5a + -7a = -2a -10 + -2a = 7a + -7a Combine like terms: 7a + -7a = 0 -10 + -2a = 0 Add '10' to each side of the equation. -10 + 10 + -2a = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -2a = 0 + 10 -2a = 0 + 10 Combine like terms: 0 + 10 = 10 -2a = 10 Divide each side by '-2'. a = -5 Simplifying a = -5
| (2x-5)(2x+5)=equation | | 45xy-72zw= | | 9m^2-4/49 | | (2x^2-3x)(3x^2+2x-1)=equation | | (x+7)(3x-2)=equation | | Y=-0.4x(x-14) | | 6/x-2=-5 | | (4x^2+7x)(5x^2-3x)=equation | | 7m^2+45mn-28n^2=0 | | 2(9/8-x/10)+x/3=5 | | x^2+16-17=0 | | X-10x+25=45 | | .06+(.10-.06)1.2= | | (4x^2-3x)(5x^2-6x+2)=equation | | x=2v+at^2 | | (5x^2+2x)(3x^2-7x+4)=equation | | x^4+4x^3-15x^2-18=0 | | 1/10*31/10 | | (4x-5)(4x+5)=equation | | 4+2m-2=9m+34-3m | | (-4.9)(7.2)= | | 1.2p-3.6=0.6p-6.4-2.6p | | (x^2-5x)(2x^2+x-3)=equation | | (1/4)+(2/x)=(11/4x) | | 1/3c-(-5)=11 | | y^2-14y=-26 | | y+10=-4 | | 3+n/4=-11 | | 5x-6=2(3x-1)-x | | 2x=(x+11)2 | | -5x-4(x-6)=12 | | (x)+3=5 |